Dual-stimuli responsive and reversibly activatable theranostic nanoprobe for precision tumor-targeting and fluorescence-guided photothermal therapy - Xu Zhao (Nature Portfolio, 2017)
A number of nanomaterials for dual diagnostic and therapeutic application have a number of limitations including poor signal-to-noise ratio. Here, the authors developed dual stimuli-responsive and reversibly activatable nanoprobes for tumour targeting and fluorescence-guided photothermal therapy.